Hubungan Jumlah Peresepan Obat Terhadap Potensially Inapropriate Medications Berdasarkan Beers Criteria 2019 Pasien Diabetes Mellitus - Kumala Sari Poespita Dewi Wahyuni; Esti Ambar Widyaningrum; Erni Anika Sari; Dwitania Noerhalizah (Indonesian Journal of Pharmaceutical Education, 2023)
Diabetes melitus can lead to complications if not controlled, the risk of complications in geriatric patiens can lead to an increase in the number of drugs prescribed, so that many geriatric receive polypharmacy drugs. Polypharmacy can be used as a factors to describe Potentially Inappropriate Medications. Potentially Inappropriate Medications are the potential for inappropriate drug use which causes a risk of side effects where there are alternative drug options for the same therapy. This study was to determine the number of drug prescribing for Potentially Inappropriate Medications based on the 2019 Beers Criteria. This studi was an observational descriptive study using retrospective data. The sample used was 195 prescriptions for patients with diabetes mellitus in the period October-December 2020 with purposive sampling technique. Characteristics of the data using the contingency coefficient correlation test. The number of drug prescriptions obtained, a total of 68.21% of patients received 5 kinds of drugs in one prescription based on the assessment of the incidence of Potentially Inappropriate Medications, there were 92.82% of prescriptions indicate an incidence of Potentially Inappropriate Medications. The highest number of Potentially Inappropriate Medications received was category one namely 50,38%. There are difference in the categories of Potentially Inappropriate Medications that patients receive due to diseases suffered by geriatricians where disease that affect many organs cause geriatricians to receive many drugs in health services. Based on a p-value of 0,000 there is a statistically significant relationship between the amount of drug administration with Potentially Inappropriate Medications.